Electrotactile displays: taxonomy, cross-modality, psychophysics and challenges - Ray, Rahul Kumar; Kumar Vasudevan, Madhan; Manivannan, M. (Frontiers in Virtual Reality, 2024)
Touch is one of the primary senses, and the receptors for touch sense are spread across the whole human body. Electrotactile displays provide tactile feedback to generate different sensations (such as tickling, tingling, itching, and pressure) in human-computer interfaces or man-machine interactions. These displays encode tactile properties, such as shape and texture, facilitating immersive experiences in virtual or remote environments. Their compact form factor and low maintenance requirements render them versatile for myriad applications. This paper is a comprehensive survey of the design and implementation of electrotactile displays, elucidating their taxonomy, cross-modal integration strategies, and psychophysical underpinnings.Emphasizing the crucial role of psychophysics, it delineates how human perception informs the design and utilization of electrotactile displays. Furthermore, this paper identifies prevalent challenges in electrotactile displays and outlines future directions to advance their development and deployment.